Determination of Chromium in blood serum using Atomic Absorption Spectrophotometric (AAS) - Khathi , Mohammed T.; Abdulwahab , Abeer Q.; Kareem , Zainab M. (University of Thi-Qar Journal, 2019)
A new approach for the direct determination of chromium by Electrothermal Atomic Absorption spectrometry (ETAAS) is proposed, the method employs a 1.0 cm X 0.3 cm Tantalum metal coil placed in graphite tube. The experimental conditions for the determination of chromium via this method have been optimized. Pyrolysis and atomization curves are constructed using uncoated graphite tube without and with coil. The calibration curves were linear over the rang 10- 50 ng/ml of chromium concentration, with relative standard deviation values, at 0.013, 0.018 and 0.024µg/ml. the accuracy and precision of the method was evaluated by determining recoveries percentage between (99.7-101) and standard deviation and using different concentrations of standard solutions of this method was applied successfully for the determination of chromium in human blood serum.